Study of Determinants Maternal Behavior in Basic Immunization for Infants in the Working Area of Banda Aceh City Health Center - Cut Fauziah; Rachmad Suhanda; Said Usman; Irwan Saputra; T. Maulana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Immunization is an effort to provide immunity to infants and children by introducing vaccines into the body. This vaccine stimulates the body to produce antibodies that function to prevent certain diseases. The coverage of Complete Basic Immunization in Banda Aceh City/District from 2022 to 2024 has decreased each year by (43.9%) in 2022, (37.8%) in 2023, and (34.9%) in 2024. The immunization coverage is still very low and below the national target of (95%). To determine the factors influencing maternal behavior in basic immunization within the working area of the Banda Aceh City Health Center. Research. Quantitative research with a Cross Sectional Study approach using primary data. The population in this study consists of all mothers with infants aged 6-11 months within the working area of the Banda Aceh City Health Center. The sample in this study consisted of 200 respondents, with data collection methods using questionnaires and analyzed univariately to describe the distribution and proportion, as well as bivariately. Bivariate data analysis with Spearman correlation test. This study found a relationship between each variable and maternal behavior regarding basic immunization with the variables Attitude Toward Immunization (p=0.000), Subjective Norm of Immunization (p=0.000), Perceived Behavioral Control of Immunization (p=0.000), Actual Behavioral Control of Immunization (p=0.000). All variables are related to maternal behavior in basic immunization within the working area of the Banda Aceh City health center.